Implementing Electronic Health Records in Philippine Primary Care Settings: Mixed-Methods Pilot Study - Anton Elepaño; Carol Stephanie Tan-Lim; Mark Anthony Javelosa; Regine Ynez De Mesa; Mia Rey; Josephine Sanchez; Leonila Dans; Antonio Miguel Dans (JMIR Medical Informatics)
Abstract BackgroundBetween 2020 and 2022, the Philippine Primary Care Studies program, a government-funded initiative supporting universal health care implementation, piloted two electronic health records (EHR) systems across urban, rural, and remote primary care sites. ObjectiveThe study aimed to evaluate the implementation of two EHR systems in diverse primary care settings in the Philippines over a three-year period. MethodsThis implementation study used an explanatory mixed methods design. Two EHR systems were deployed: an Open Medical Records System (OpenMRS)-based platform in 2016, and a Microsoft-based system in 2021. Both systems integrated clinical documentation, pharmacy, laboratory, and reporting modules. Implementation strategies included training workshops and materials, iterative user feedback loops, and infrastructure cofinancing with local governments. Surveys were administered yearly to all end users. The primary outcome was behavioral intention to use the system. Quantitative data were supplemented by inductive content analysis of qualitative responses to explain observed trends. ResultsA total of 351 survey responses were collected from 2020 to 2022. In 2020, the intention to use the OpenMRS-based EHR was high across all sites. By 2022, following the launch of the Microsoft-based EHR, acceptability declined significantly among doctors and administrative staff, particularly at the urban site. In contrast, the remote site which retained the OpenMRS-based system maintained high acceptability levels. Qualitative findings revealed that while the new EHR system provided a more privacy-focused design, users preferred a cross-platform EHR to allow more flexible access to patient data. At the rural site where the EHR was used to facilitate task-shifting among nurses involved in clinical management, users were less impacted by this shift. ConclusionsThe disparities in EHR acceptability across urban, rural, and remote sites were influenced by contextual, technical, and demographic factors. The decline in acceptability following the EHR system transition highlights the importance of implementation strategies that reflect the specific needs and capacities of each setting. These findings offer practical insights for adapting EHR systems to diverse primary care contexts.